2009
DOI: 10.1038/nrc2733
|View full text |Cite
|
Sign up to set email alerts
|

The role of supercoiling in transcriptional control of MYC and its importance in molecular therapeutics

Abstract: MYC is deregulated in most tumour types, but an effective means to selectively target its aberrant expression is not yet available. Supercoiling that is induced by transcription has been demonstrated to have dynamic effects on DNA in the MYC promoter element: it converts duplex DNA to non-duplex DNA structures, even at considerable distances from the transcriptional start site. These non-duplex DNA structures, which control both turning on and off of transcription and the rate of transcription firing, are amen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
273
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(279 citation statements)
references
References 127 publications
6
273
0
Order By: Relevance
“…With MYC's role in so many hallmarks of cancer, and growth related events, it is easy to understand why its deregulation is found so frequently as either a causative oncogenic event, or distinctly tied to prognosis and therapy. It is also something to which cancer cells often seem addicted, providing a window of opportunity for new anticancer therapies (15). Specific targeting of protein function has yet to be a successful avenue of drug development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With MYC's role in so many hallmarks of cancer, and growth related events, it is easy to understand why its deregulation is found so frequently as either a causative oncogenic event, or distinctly tied to prognosis and therapy. It is also something to which cancer cells often seem addicted, providing a window of opportunity for new anticancer therapies (15). Specific targeting of protein function has yet to be a successful avenue of drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of Protein Binding to the MYC NHE III 1 with GQC-05-Many extensive studies have been performed to describe the binding of transcription factors to the MYC core promoter, as well as the resolution and stabilization of the MYC promoter G4 (15,33,34,49). Using GQC-05, we monitored the modulation of the known transcriptional factors and regulatory proteins bound to the NHE III 1 region of MYC and showed that within six to twelve hours of small molecule administration, most of these proteins were significantly decreased in both BL cell lines (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…64 Accordingly, in silico analyses showed a high enrichment of these sequences at regulatory regions of the genome and, notably, at the promoters of a wide range of oncogenes. [85][86][87][88] In addition, several conformation-sensitive proteins with regulatory function bind and stabilize non-B DNAs, suggesting an important role of these structures in transcriptional output. 64 Another way to make genetic processes more tolerant to the constrained DNA topology is weakening the DNA through introducing double strand breaks or nicks.…”
Section: Dna Topology and Genome Architecturementioning
confidence: 99%
“…It remains largely unexplored as to how this pathway is regulated under normal or stressed conditions. Among numerous notable transcriptional factors, cMyc is well known to regulate up to 10%-15% human genes involved in cell cycle, development, apoptosis and metabolism [32][33][34]. Interestingly, it has been suggested recently that cMyc is posed to amplify all the extant expressed genes [35,36].…”
Section: Introductionmentioning
confidence: 99%